2004
DOI: 10.1017/s002211200400789x
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study on stationary history effects in high-frequency Stokes flows

Abstract: We report results of a series of detailed experiments designed to unveil the dynamics of a particle of radius $a$ moving in high-frequency, low-Reynolds-number oscillatory flow. The fundamental parameters in the problem are the Strouhal ($\hbox{\it Sl}$) and the particle Reynolds numbers ($\hbox{\it Re}_p$), as well as the fluid-to-particle density ratio $\alpha$. The experiments were designed to cover a range of $\hbox{\it Sl} \hbox{\it Re}_p$ from 0.015 to 5 while keeping $\hbox{\it Re}_p < 0.5$ and $\hbox{\… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
32
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 14 publications
4
32
0
Order By: Relevance
“…The latter authors, in particular, found the relative importance of history force for 1 to be particularly significant for St v 0.3 (more specifically, it was found to attain a maximum value for a dimensional frequency approaching the value 9/ 2 R and displacement amplitudes b smaller than the radius R of the particle, conditions that using the present reference units would read: 2PrSt -1 =1.6x10 5 and / 2 (9St/2) 1/2 2x10 -2 ). Albeit the importance of the Basset term was observed to decrease rapidly as the value of St v approached 0 for all values of  (as confirmed later in the experiment by Coimbra et al, 2004), however, they found the ratio of the Basset force to the overall force experienced by the particle (virtual mass + stokes drag + history term) to be 0.2 (see Figure 1 of their work) for a value of their control parameter S=0.06, which corresponds to the present 10 4 . As the studies by Vojir and Michaelides (1994) and Coimbra and Rangel (2001), both indicate that the Basset term may play a potentially significant role for the conditions considered in the present study when >5x10 3 , it has been therefore deemed necessary to assess expressly its influence on PAS for relatively high frequencies (the results of this study will be discussed in Sect.…”
Section: The Dispersed Phasesupporting
confidence: 69%
“…The latter authors, in particular, found the relative importance of history force for 1 to be particularly significant for St v 0.3 (more specifically, it was found to attain a maximum value for a dimensional frequency approaching the value 9/ 2 R and displacement amplitudes b smaller than the radius R of the particle, conditions that using the present reference units would read: 2PrSt -1 =1.6x10 5 and / 2 (9St/2) 1/2 2x10 -2 ). Albeit the importance of the Basset term was observed to decrease rapidly as the value of St v approached 0 for all values of  (as confirmed later in the experiment by Coimbra et al, 2004), however, they found the ratio of the Basset force to the overall force experienced by the particle (virtual mass + stokes drag + history term) to be 0.2 (see Figure 1 of their work) for a value of their control parameter S=0.06, which corresponds to the present 10 4 . As the studies by Vojir and Michaelides (1994) and Coimbra and Rangel (2001), both indicate that the Basset term may play a potentially significant role for the conditions considered in the present study when >5x10 3 , it has been therefore deemed necessary to assess expressly its influence on PAS for relatively high frequencies (the results of this study will be discussed in Sect.…”
Section: The Dispersed Phasesupporting
confidence: 69%
“…Important applications of FC can be found in many areas of science, from electrochemistry [20], to physics [21,22], fluid mechanics [23], mechanical systems [24], other areas of engineering [25][26][27][28], and biology [29][30][31].…”
Section: Fractional Calculus -Brief Summarymentioning
confidence: 99%
“…The increased interest in fractional systems in the past few decades is due mainly to a large body of physical evidence describing fractional order behavior in diverse areas such as fluid mechanics, mechanical systems, rheology, electromagnetism, quantitative finances, electrochemistry, and biology. Fractional order modeling provides exceptional capabilities for analysing memory-intense and delay systems and it has been associated with the exact description of complex transport phenomena such as fractional history effects in the unsteady viscous motion of small particles in suspension (Coimbra et al 2004, L'Esperance et al 2005. Although fractional order dynamical and control systems were studied only marginally until a few decades ago, the recent development of effective mathematical methods of integration of non-integer order differential equations (Charef et al (1992); Coimbra & Kobayashi (2002), Diethelm et al (2002); Momany (2006), Diethelm et al (2005)) has resulted in a number of control schemes and algorithms, many of which have shown better performance and disturbance rejection compared to other traditional integer-order controllers (Podlubni (1999); Hartly & Lorenzo (2002), Ladaci & Charef (2006), among others).…”
Section: Introductionmentioning
confidence: 99%